2022
DOI: 10.1136/bmjopen-2021-056904
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to healthcare and self-reported adverse outcomes for autistic adults: a cross-sectional study

Abstract: ObjectivesAutistic people experience poor physical and mental health along with reduced life expectancy compared with non-autistic people. Our aim was to identify self-reported barriers to primary care access by autistic adults compared with non-autistic adults and to link these barriers to self-reported adverse health consequences.DesignFollowing consultation with the autistic community at an autistic conference, Autscape, we developed a self-report survey, which we administered online through social media pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 22 publications
6
91
0
2
Order By: Relevance
“…Maddams and Pearson (2013) found that autistic patients identified ease of access to GPs (such as timing and location of visits and flexibility of appointment times), patient anxiety prior to a consultation, and communication between doctor and patient during a consultation as the most difficult issues prior to and during a consultation with their GP. Doherty et al (2022) also identified these issues. Many GPs are likely to find it counter-intuitive that autistic people with no ID often have difficulty in accessing health care, many aspects of autism being difficult for non-autistic people to understand (Beardon, 2017).…”
Section: Annual Health Checks (Ahcs)mentioning
confidence: 99%
See 3 more Smart Citations
“…Maddams and Pearson (2013) found that autistic patients identified ease of access to GPs (such as timing and location of visits and flexibility of appointment times), patient anxiety prior to a consultation, and communication between doctor and patient during a consultation as the most difficult issues prior to and during a consultation with their GP. Doherty et al (2022) also identified these issues. Many GPs are likely to find it counter-intuitive that autistic people with no ID often have difficulty in accessing health care, many aspects of autism being difficult for non-autistic people to understand (Beardon, 2017).…”
Section: Annual Health Checks (Ahcs)mentioning
confidence: 99%
“…Many GPs are likely to find it counter-intuitive that autistic people with no ID often have difficulty in accessing health care, many aspects of autism being difficult for non-autistic people to understand (Beardon, 2017). The difficulty accessing healthcare applies both to individuals who have received a formal diagnosis of autism and to those who have self-identified as autistic, and leads to adverse health outcomes (Doherty et al, 2022).…”
Section: Annual Health Checks (Ahcs)mentioning
confidence: 99%
See 2 more Smart Citations
“…During a review of common online epilepsy peer support platforms (MyEpilepsyTeam, Brain Ablaze, Facebook groups and #epilepsy threads in Twitter, Instagram and TikTok), it became apparent that people with epilepsy require advice which is not being addressed through media supplied for patient use by healthcare/clinical services. Lived experience accounts detail the difficulties with asking questions at appointments: embarrassment (11), focus on clinical issues (12), not wanting to "waste clinicians time" (13), not having a relationship with the clinician (14), and forgetting to ask/lack of understanding (15). A virtual platform provides a forum to pose questions when they arise, using an anonymous format.…”
Section: Introductionmentioning
confidence: 99%